Library Roles in University Research Assessment - MacColl, John (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
This article summarises the findings of two OCLC research reports which recently documented how university research is assessed in five countries and the role research libraries play in the various schemes. Libraries’ administrative role in supplying bibliometrics is the most obvious. However, the author advocates a much more strategic role for libraries: to focus on the scholarly activity all around the library, to curate, advise on and preserve the manifold outputs of research activity.